Plowing the sea - Fairbanks, Michael (Boston, 1997)
The authors address the issue of competitiveness in the developing world. Using the Colombian cut-flower industry as a backdrop (and drawing from a variety of industries in Bolivia, Venezuela, and Peru), they identify seven core elements of the failed model of competitiveness in which much of the developing world appears to be trapped. These patterns include an over-reliance on basic production factors and natural resources, inadequate supplier and distributor relationships, and insufficient tools for performing customer and competitor analysis. In a challenge to conventional economic development theory and practice, Fairbanks and Lindsay propose an "action framework, " emphasizing strategic and microeconomic approaches to growth, based on a partnership between the public and private sectors. The authors argue that only by identifying common goals, committing to a long-term perspective, investing in human resources, and assigning new leadership roles for businesspeople and policymakers alike, can developing countries break out of the vicious cycle of underperformance.
Keywords: Industries-Case studies